Evaluation of various patient-, lesion-, and procedure-related factors on the occurrence of pneumothorax as a complication of CT-guided percutaneous transthoracic needle biopsy - Shiekh, Yassar (Pol J Radiol, 2019)
PURPOSE: To assess the influence of various patient-, lesion-, and procedure-related variables on the occurrence of pneumothorax as a complication of CT-guided percutaneous transthoracic needle biopsy. MATERIAL AND METHODS: In a total of 208 patients, 215 lung/mediastinal lesions (seven patients were biopsied twice) were sampled under CT guidance using coaxial biopsy set via percutaneous transthoracic approach. Incidence of post procedure pneumothorax was seen and the influence of various patient-, lesion-, and procedure-related variables on the frequency of pneumothorax with special emphasis on procedural factors like dwell time and needle-pleural angle was analysed. RESULTS: Pneumothorax occurred in 25.12% (54/215) of patients. Increased incidence of pneumothorax had a statistically significant correlation with age of the patient (p = 0.0020), size (p = 0.0044) and depth (p = 0.0001) of the lesion, and needle-pleural angle (p = 0.0200). Gender of the patient (p = 0.7761), emphysema (p = 0.2724), site of the lesion (p = 0.9320), needle gauge (p = 0.7250), patient position (p = 0.9839), and dwell time (p = 0.9330) had no significant impact on the pneumothorax rate. CONCLUSIONS: This study demonstrated a significant effect of the age of the patient, size and depth of the lesion, and needle-pleural angle on the incidence of post-procedural pneumothorax. Emphysema as such had no effect on pneumothorax rate, but once pneumothorax occurred, emphysematous patients were more likely to be symptomatic, necessitating chest tube placement. Gender of the patient, site of the lesion, patient position during the procedure, and dwell time had no statistically significant relation with the frequency of post-procedural pneumothorax. Surprisingly, needle gauge had no significant effect on pneumothorax frequency, but due to the small sample size, non-randomisation, and bias in needle size selection as per lesion size, further studies are required to fully elucidate the causal relationship between needle size and post-procedural pneumothorax rate. The needle should be as perpendicular as possible to the pleura (needle-pleural angle close to 90°), to minimise the possibility of pneumothorax after percutaneous transthoracic needle biopsy.